2023
DOI: 10.3390/curroncol30010046
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Emotional and Mental Impact on Cancer Patients Receiving Radiotherapy: An Interpretation of Potential Explaining Descriptors

Abstract: Background: Significant changes in the accessibility and viability of health services have been observed during the COVID-19 period, particularly in vulnerable groups such as cancer patients. In this study, we described the impact of radical practice and perceived changes on cancer patients’ mental well-being and investigated potential outcome descriptors. Methods: Generalized anxiety disorder assessment (GAD-7), patient health (PHQ-9), and World Health Organization-five well-being index (WHO-5) questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…It was found that this information is mainly provided by accounts or users who do not identify themselves as healthcare professionals or health institutions. This trend can be observed in other studies analyzing YouTube as a source of information for pathologies such as diabetes [ 27 ], cancer [ 3 , 5 , 9 , 18 ], dermatological conditions such as psoriasis [ 25 ], and even vaccination against SARS-CoV-2 during the COVID-19 pandemic [ 47 ]. However, this situation is not exclusive to YouTube, as it has also been found in other social networks based on written communication, such as Twitter, also in pathologies such as cancer [ 20 , 48 ] and even in primary prevention strategies such as vaccination against the COVID-19 pandemic [ 48 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It was found that this information is mainly provided by accounts or users who do not identify themselves as healthcare professionals or health institutions. This trend can be observed in other studies analyzing YouTube as a source of information for pathologies such as diabetes [ 27 ], cancer [ 3 , 5 , 9 , 18 ], dermatological conditions such as psoriasis [ 25 ], and even vaccination against SARS-CoV-2 during the COVID-19 pandemic [ 47 ]. However, this situation is not exclusive to YouTube, as it has also been found in other social networks based on written communication, such as Twitter, also in pathologies such as cancer [ 20 , 48 ] and even in primary prevention strategies such as vaccination against the COVID-19 pandemic [ 48 ].…”
Section: Discussionsupporting
confidence: 55%
“…The need to obtain information about a cancer diagnosis is so necessary for patients to know something such as treatments, side effects, or even how to live with cancer [ 7 ] through cancer survivor testimonies [ 8 ]. But it is necessary not to forget the mental well-being associated with the access to information; this access reduces anxiety, depression, and even frustration, and is something essential to improve the emotional and mental well-being of patients who have received a diagnosis of cancer, as well as their families [ 8 , 9 ]. Although, in many cases, the main source of information is healthcare professionals [ 10 , 11 ], it is true that doubts and questions sometimes cannot wait, at which point patients or family members seek information in the most accessible way possible, which is using the Internet [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the inclusion period of the pilot, there was a continued impact of COVID-19. This impacted upon the rate of inclusion, and there may have also been potential effects on the psychosocial well-being of the patients that should be considered [25,26]. This should be taken into account when interpreting the study results and depressive symptoms identified.…”
Section: Discussionmentioning
confidence: 99%
“…This could worsen outcomes since psychological discomfort in cancer patients has been reported to lead to a negative impact on their physical health, treatment adherence, and quality of life [ 13 , 14 ]. COVID-19 may have exacerbated the burden of cancer, and it is crucial that we identify the factors associated with the increasing prevalence of such mental health concerns [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%